Transport phenomena in dispersed media - Kelbaliev, G. I. e uthor; Tagiyev, D. B.; Rasulov, S. R. (Boca Raton : CRC Press, 2020)
Transport Phenomena in Dispersed Media addresses the main problems associated with the transfer of heat, mass and momentum. The authors focus on the analytical solutions of the mass and heat transfer equations; the theoretical problems of coalescence, coagulation, aggregation and fragmentation of dispersed particles; the rheology of structured aggregate and kinetically stable disperse systems; the precipitation of particles in a turbulent flow; the evolution of the distribution function; the stochastic counterpart of the mass transfer equations; the dissipation of energy in disperse systems; and many other problems that distinguish this book from existing publications. Key Selling Features Covers all technological processes taking place in the oil and gas complex, as well as in the petrochemical industry Presents new original solutions for calculating design as well as for the development and implementation of processes of chemical technology Organized to first provide an extensive review of each chapter topic, solve specific problems, and then review the solutions with the reader Contains complex mathematical expressions for practical calculations Compares results obtained on the basis of mathematical models with experimental data
Preface Nomenclature Authors Introduction Chapter 1 Hydrodynamics of the Flow of Liquids and Dispersion Media Chapter 2 Heat Transfer and Energy Dissipation Chapter 3 Introduction to Mass Transfer Chapter 4 The Basic Laws of Mass Transfer and Diffusion Chapter 5 Convective Mass Transfer Chapter 6 Analytical Solutions of the Problem of Mass Transfer with Different Peclet Numbers Chapter 7 Hydrodynamics and Mass Transfer in Non-Newtonian Fluids Chapter 8 Aggregate and Sedimentation Unstable Dispersion Systems Chapter 9 Stochastic Analogue of Mass Transfer Equations and Practical Applications References Index
OCLC-licensed vendor bibliographic record.
Keywords: Mass transfer; Heat -- Transmission; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical